On the structure of the automorphism group of certain automorphic loop. Issue 5 (4th May 2017) - Merlini Giuliani, Maria de Lourdes; dos Anjos, Giliard Souza
ABSTRACT: Automorphic loops, or A -loops, are loops in which all inner mappings are automorphisms. We investigated A -loops arising from a Lie algebra and describe their automorphism group. Also, we identify and describe their inner mapping group.